Frequência de ocorrência de cavidade anoftálmica na região centro-oeste paulista e características dos portadores - De Sousa, Roberta Lilian Fernandes [UNESP]; Marãon, Andrã Ricardo Carvalho [UNESP]; Padovani, Carlos Roberto [UNESP]; Schellini, Silvana Artioli [UNESP] (FapUNIFESP (SciELO), 2013)
Purpose: To observe the frequency of the occurrence of the anophthalmic socket in the Middle West region of the state of São Paulo and to describe the demographic profile of the carriers in a population-based data. Methods: A cross-sectional study involve a random sampling carried out in twelve cities of the Middle West region of the state of São Paulo, for which the reference center is the city of Botucatu was done. The participators were chosen by assortment which considered the houses of these people. It was established a sampling with 11,453 people. All the exams were realized using a Mobile Ophthalmologic Unit. The research protocol included the demographic data and the complete ophthalmologic exam (anamnesis, ocular and systemic antecedents, familiar antecedents, visual acuity with and without correction, tonometry, biomicroscopy, fundoscopy, and refraction exam). All the data were transferred to an Excel spreadsheet and submitted to a descriptive analysis and were presented by the frequency of the occurrence. Results: Ophthalmic socket frequency in the Middle West region of the state of São Paulo was 0.96%. We found 11 cases of anophthalmic socket, with involvement of 0.7 % in females and 1.3 %, male. The most common causes of anophthalmic socket were glaucoma (blind painful eye), microphthalmia, trauma, and endophthalmitis. The majority of the people were 40 years old or more, and we found just one person younger than 19 years old. Conclusion: The anophthalmic socket occurred in 0.96% of the habitants of the Middle West region of São Paulo State, occurring mainly in male and with large variety of the affected ages.
Frequency of occurrence of anophthalmic socket in the middle west region of the state of são paulo and the carriers characteristics
Keywords: Anophthalmic socket; Cross-sectional studies; Epidemiology; Ophthalmologic surgical procedures; Population surveillance